Optimization control strategy for active distribution areas with E-SOP considering energy storage characteristics - Weixu YU; Yewen WEI; Peng YUAN; Sijia ZHANG; Zhipeng ZHOU; Jie ZHANG (电力工程技术)
To address issues such as reverse power flow, voltage fluctuations, and insufficient power supply capacity resulting from the increased penetration of distributed generation in distribution networks, an optimized control strategy for active distribution substations incorporating a three-terminal intelligent soft open point (E-SOP) for energy storage is proposed. Firstly, the topology of E-SOP is thoroughly analyzed, and a corresponding mathematical model is established to lay the foundation for subsequent optimization control. Secondly, a site selection and planning model for the E-SOP based on voltage-power sensitivity is proposed to determine its optimal installation location. On this basis, a multi-objective optimization model is developed, aiming to minimize comprehensive costs and voltage deviations, to configure the capacity of the E-SOP. This model is transformed into a second-order cone programming model using conic relaxation techniques and solved iteratively through a particle swarm optimization algorithm. Finally, simulations on an IEEE 33-node flexible interconnected system validate the effectiveness of the proposed strategy, and further simulations on an IEEE 69-node system confirm its applicability and superiority. The results indicate that, compared to traditional systems without E-SOP interconnection, the proposed strategy reduces voltage deviation by 2.24%, daily average system losses by 50.41%, and overall costs by 21.74%, making it suitable for distribution systems of various scales.